Religious Education Policies of Republican People’s Party (1923-1950) And Democrat Party (1950-1960) in Turkey - Hasan Gurbuz (International Journal of Social Sciences & Educational Studies, 2023)
The decline in the influence of religion in social life in the face of modernization movements pointed to a new world in which secular paradigms prevailed. As a matter of fact, the Republic of Turkey, founded in 1923, started its revolutionary transformations in the field of education. First of all, they took religious education under the control of the state and opened new institutions. However, due to the indifference of the society to these institutions, they closed them completely in 1933. Afterwards, they did not put the issue of religious education on their agenda again until 1946. However, during this period, the political conditions all over the world changed and the need for democratization of Turkey emerged. In this period, when it was opposed by another party for the first time, the Republican People’s Party put religious education on its agenda. However, it seems that they approached this issue rather reluctantly. The Democrat Party, which came to power later on, took very important steps regarding religious education and tried to meet the demands of the society. However, at the same time, it was criticized by the secular elite for taking steps against the republican revolutions.